Use of perioperative prophylactic antibiotics following excision of ulcerated skin lesions in the UK: a national, multispeciality survey of clinicians. (1st May 2022) - Totty, Joshua Philip; Matin, Rubeta N.; Wernham, Aaron; Ray, Ruby; Thomas‐Jones, Emma; Abbott, Rachel Angharad
Summary: Skin cancer is the most common malignancy in the UK, and up to a third of lesions are ulcerated at the time of excision. Ulceration has been shown to increase the risk of developing surgical site infection following excision, with some studies finding infection rates of 33%. However, no specific guidelines for the use of antibiotic prophylaxis in such cases exist. We surveyed 129 clinicians (covering Dermatology, Plastic Surgery, Ear, Nose and Throat Surgery, and Oral and Maxillofacial Surgery) who all excise skin lesions on a regular basis. There was significant variability in their practice with regard to antibiotic prophylaxis, with 9% always prescribing them and 19% never prescribing them. Variation exists both among and between specialities. This variation increases the risk of antimicrobial resistance and shows a paucity of good clinical evidence, indicating that a well‐designed clinical trial is needed to guide future practice.